Two short sequences from amaranth 11S globulin are sufficient to target green fluorescent protein and beta-glucuronidase to vacuoles in Arabidopsis cells - Petruccelli, Silvana (Plant physiology and biochemistry : PPB, 2007)
Vacuolar sorting of seed storage proteins is a very complex process since several sorting pathways and interactions among proteins of different classes have been reported. In addition, although the C-terminus of several 7S proteins is important for vacuolar delivery, other signals seem also to be involved in this process. In this work, the ability of two sequences of the Amaranthus hypochondriacus 11S globulin (amaranthin) to target reporter proteins to vacuoles was studied. We show that the C-terminal pentapeptide (KISIA) and the GNIFRGF internal sequence fused at the C terminal region of genes encoding secretory versions of green fluorescent protein (GFP) and GFP-beta-glucuronidase (GFP-GUS) were sufficient to redirect these reporter proteins to the vacuole of Arabidopsis cells. According to the three-dimensional structure of 7S and 11S storage globulins, this internal vacuolar sorting sequence corresponds to the alpha helical region involved in trimer formation, and is conserved within these families. In addition, these sequences were able to interact in vitro, in a calcium dependent manner, with the sunflower vacuolar sorting receptor homolog to pea BP-80/AtVSR1/pumpkin PV72. This work shows for the first time the role of a short internal sequence conserved among 7S and 11S proteins in vacuolar sorting